2015
DOI: 10.1016/j.intell.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The structure of intelligence in children with specific learning disabilities is different as compared to typically development children

Abstract: Children with specific learning disabilities (SLDs) are characterized by a poor academic achievement despite an average intelligence. They are therefore typically assessed not only with achievement tests, but also with intelligence tests, usually the Wechsler Intelligence Scale for Children (WISC). The assumption of a discrepancy between IQ and achievement in children with SLD has been questioned, however, and the implications of using different measures in batteries of intellectual subtests have not been thor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
53
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 37 publications
13
53
2
3
Order By: Relevance
“…First, in agreement with previous studies, we found that children with DD failed in a WM task in which they were asked not only to recall, but also to manipulate and process previously presented information Passolunghi & Siegel, 2001;Schuchardt, et al, 2008;Swanson & Sachse-Lee, 2001;Szűcs, 2016). It is also well known that the general cognitive profile of children with specific learning disorders shows impairment in WM and processing speed indexes (Giofrè & Cornoldi, 2015;Toffalini, et al 2017). Additionally, to better understand the role of WM impairments in DD and MA groups, we compared their performances with the combined group (i.e., MA-DD).…”
Section: Discussionsupporting
confidence: 91%
“…First, in agreement with previous studies, we found that children with DD failed in a WM task in which they were asked not only to recall, but also to manipulate and process previously presented information Passolunghi & Siegel, 2001;Schuchardt, et al, 2008;Swanson & Sachse-Lee, 2001;Szűcs, 2016). It is also well known that the general cognitive profile of children with specific learning disorders shows impairment in WM and processing speed indexes (Giofrè & Cornoldi, 2015;Toffalini, et al 2017). Additionally, to better understand the role of WM impairments in DD and MA groups, we compared their performances with the combined group (i.e., MA-DD).…”
Section: Discussionsupporting
confidence: 91%
“…In fact, the relationship between digit span and GAI is stronger for the backward than for the forward version in TDC, whereas in children with SLD the relationship is generally weaker and does not differ significantly between the backward and forward versions of the task. These findings are in line with the hypothesis that intelligence is organized differently in TDC and SLD children (Giofrè & Cornoldi, 2015). Even if the differences in the correlations among the TDC versus the SLD groups may actually seem not large (.10 and .25 in TDC versus .15 and .10 in SLD), however, this small difference in the correlation pattern may be particularly relevant for explaining the observation that the overall g-content of these tasks at the latent level is reduced in the case of SLD (Giofrè & Cornoldi, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…The digit span subtest was included in all the latest versions of the WISC battery and in all its various international adaptations. Digit span has often been considered in studies examining STM performance in children with SLD, recording a standardized difference between SLD and TDC groups ranging from .65 to .71 (Giofrè & Cornoldi, 2015;Styck & Watkins, 2014), resembling the figure reported by Melby-Lervag and coauthors (2012) for all STM measures. But research conducted to date has not systematically investigated the potential differences between the two classical versions (forward and backward) of the digit span task, both of which are included in the WISC battery.…”
Section: Forward and Backward Digit Span Difficulties In Children Witmentioning
confidence: 69%
See 1 more Smart Citation
“…However, the specific VCI-PRI pattern in spelling disorder differed from that in reading disorder, as in the former case the two indexes were not differentiated, while in reading disorder there was a superiority of PRI over VCI. Note that reading and spelling disorder were marked by a GAI in the normal range but significantly higher than the normative sample; as the GAI index is known to be more related to g-factor than the CPI (Giofrè & Cornoldi, 2015). This may suggest that the core intellectual functions could be even above average in certain categories of children who receive a diagnosis of SLD.…”
Section: Discussionmentioning
confidence: 87%